2019
DOI: 10.1183/23120541.00014-2019
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers are associated with aetiology and predict outcomes in community-acquired pneumonia: results of a 5-year follow-up cohort study

Abstract: BackgroundBiomarkers may facilitate clinical decisions in order to guide antimicrobial treatment and prediction of prognosis in community-acquired pneumonia (CAP). We measured serum C-reactive protein, procalcitonin (PCT) and calprotectin levels, and plasma pentraxin 3 (PTX3) and presepsin levels, along with whole-blood white cell counts, at three time-points, and examined their association with microbial aetiology and adverse clinical outcomes in CAP.MethodsBlood samples were obtained at hospital admission, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
(57 reference statements)
2
25
0
1
Order By: Relevance
“…Besides, multiple studies have identified an association of respiratory infectious disease and inadequate serum vitamin D in nonrachitic children [13], [14]. Biomarkers, applied in synergy with clinical signs and symptoms of pneumonia may provide extra data on disease severity and the differentiation between bacterial and viral aetiology [15], [16]. Pentraxin 3 is known as an acute-phase mediator that rapidly increases in inflammatory and infectious disorders [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, multiple studies have identified an association of respiratory infectious disease and inadequate serum vitamin D in nonrachitic children [13], [14]. Biomarkers, applied in synergy with clinical signs and symptoms of pneumonia may provide extra data on disease severity and the differentiation between bacterial and viral aetiology [15], [16]. Pentraxin 3 is known as an acute-phase mediator that rapidly increases in inflammatory and infectious disorders [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…PCT is also useful as a prognostic biomarker. High levels of PCT at hospital admission for CAP are associated with ICU admission [62] and short-term mortality [10,63]. Furthermore, the persistence of elevated levels at 72 h before the start treatment is associated with treatment failure and mortality, while PCT being decreased improves the prognostic with a lower risk of shock, ICU admission, invasive mechanical ventilation, and death [54].…”
Section: Procalcitoninmentioning
confidence: 99%
“…FGF21 is a metabolic regulator with anti-inflammatory and immunoregulatory properties [103]. Siljan et al recently evaluated the role of another biomarkers in CAP [10]. Presepsin, calprotectin, and pentraxin 3 (PTX3) are a soluble CD14-subtype molecule (sCD14-ST), a neutrophil biomarker, and a receptor involved in innate immunity, respectively.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Es fehlen prospektive Studien, die einen direkten Nutzen der zumeist in einem Multiplex-PCR-Ansatz durchgeführten Verfahren auf wichtige klinische Endpunkte wie Mortalität, stationäre Verweildauer oder auch den effizienteren Einsatz von Antibiotika zeigen. Eine Kombination von zeitnaher und sensitiver Erregerdiagnostik erscheint derzeit nur in Kombination mit neuen, prädiktiven Biomarkern eine Verbesserung aktueller Therapiealgorithmen zu erbringen [29].…”
Section: Molekulare Verfahren Zur Erregerdiagnostikunclassified